Influence of Copper Stoichiometric Composition and Compaction Method on Mechanical Properties of CuxSe Thermoelectric Materials - Fani Stergioudi; Georgios Skordaris; Maria Pappa; Nikolaos Michailidis; Vasileios Pavlidis; Dimitrios Stathokostopoulos; Aikaterini Teknetzi; Lamprini Malletzidou; George Vourlias; Georgios Maliaris; Ioanna K. Sfampa (Metals, 2025)
This study investigates the structural and mechanical properties of Cu–Se-based thermoelectric materials with varying Cu:Se stoichiometries (1.8, 1.9, and 2.0). Phase composition was examined using X-ray diffraction (XRD), revealing a transition from a mixed α/β-phase in Cu:Se = 2.0 to a fully cubic β-phase Cu2−xSe in Cu:Se = 1.8. Crystallite size analysis showed a reduction with increasing Cu content, which strongly influenced mechanical behavior. Vickers microhardness and nanoindentation tests were employed to assess hardness, elastic modulus, and elastic recovery. The Cu:Se = 2.0 sample exhibited the highest hardness but the lowest elastic recovery and elastic modulus from indentation, suggesting strong intragrain cohesion but limited elastic deformation due to fine grain structure. In contrast, the sub-stoichiometric Cu:Se = 1.8 phase displayed higher elastic modulus and recovery, possibly due to a more rigid Se sub-lattice and defect-mediated deformation mechanisms. Compression tests confirmed the higher bulk modulus in the Cu-deficient phase. Bending tests also showed that the Cu-deficient phase exhibited the highest bending modulus, further supporting its enhanced stiffness under elastic deformation. These results highlight the significant role of stoichiometry and crystallite structure in tuning the mechanical response of thermoelectric Cu–Se compounds, with implications for their durability and performance in practical applications.